Interview with Roberto Cortés Conde - De Pablo, Juan Carlos (Instituto de Economía y Finanzas. Facultad de Ciencias Económicas. Universidada Nacional de Córdoba., 2007)
Cortés Conde was born in Buenos Aires, Argentina, on February 5, 1932. He has been married to Sara Jorge since 1955, has four children and six grandchildren. He received his law degree from the University of Buenos Aires (UBA) in 1956, and did postgraduate studies in sociology, also at the UBA, between 1960 and 1962. In our country he taught political economy at the Law School of the UBA, between 1984 and 1990, and economic history at the Universidad Nacional del Litoral, between 1963 and 1966, at the Universidad Católica Argentina, between 1981 and 1990, and at the Universidad de San Andrés since 1991 (emeritus since 2002). He has taught abroad at the universities of Chicago, Harvard, Hebrew University of Jerusalem, Texas, and Yale. He is a full member of the National Academy of History and the National Academy of Economic Sciences, and between 1998 and 2002 he chaired the International Association of Economic History. His complete curriculum is available at www.udesa.edu.ar.